Interactive regulations by viruses and dissolved organic matter on the bacterial community. (18th July 2017) - Liu, Hongbin; Tan, Shangjin; Xu, Jie; Guo, Wang; Xia, Xiaomin; Yan Cheung, Shun
Abstract: Viruses and dissolved organic matter (DOM) are major top–down and bottom–up factors, respectively, which control the abundance and diversity of bacterial communities. However, the relative strength and interaction between these two regulators in different marine ecosystems are not fully understood. We applied viral reduction and cross‐transplantation of eutrophic estuarine and pristine coastal waters to examine the separate and combined effects of viruses and DOM on the bacterial community composition. We showed that bacteria were more abundant in the virus‐depleted groups, particularly in those from the eutrophic estuarine water (i.e., > 7 times higher, when compared with the virus‐rich groups). Cluster analyses showed that the bacterial communities in the virus‐rich groups were most similar to the in situ populations. Bacterial community richness, evenness and diversity were reduced at high DOM concentrations but were sustained by viruses. This allowed bacteria that were less vulnerable to viral infection to thrive (such as those in the families Alteromonadaceae, Rhodobacteraceae, Flavobacteriaceae, and SAR11), while suppressing those capable of fast growth at elevated DOM concentrations but which were more vulnerable to viral attack (such as those from the family Vibrionaceae). Our results showed that viral regulation occurring at the strain level can affect the bacterial community structure at higher phylogenetic levels. In addition, some less abundant groups, such as Vibrio and Alteromonas, might actually win the competition for resources, providing viral control is removed. Our results also showed that the population dynamics of certain bacterial groups was controlled by viruses, and the strength of such control was modulated by the concentration of DOM. We suggest that the composition of the bacterial community in aquatic environments results from the interactive regulation by DOM and viruses among other regulators.